Analisis Perbandingan Kinerja Keuangan Sebelum Dan Selama Pandemi Covid-19 Pada Perusahaan Sektor Industri Barang Konsumsi Yang Tercatat Di BEI - Alcander, Jessen; Nuraini, Airin (Institut Bisnis dan Informatika Kesatuan, 2022)
Covid-19 has had a huge impact on the whole world, not only in terms of health and humanity, but also on social and economic aspects. The company's performance is also affected by this pandemic. The formulation of the problem in this study is how to compare the financial performance conditions of companies in the consumer goods industry sector before and during the Covid 19 pandemic through the measurement variables of activity ratios, solvency ratios, liquidity ratios and profitability ratios and are there significant differences between financial performance before and during the pandemic. from this study to find out the comparison of the financial performance of companies in the consumer goods industry sector before and during the covid 19 pandemic. The type of this thesis research is quantitative research. The object of the research is the company. The data used in this thesis is secondary data obtained from the Indonesia Stock Exchange. The ratios used to measure financial performance are Profitability Ratios (Return On Assets, Return On Equity and Net Profit Margin), Liquidity Ratios (Current Ratio, Quick Ratio and Cash Ratio), Activity Ratios (Total Asset Turnover, Inventory Turnover and Fixed Asset Turnover ) and Solvency Ratio (Debt To Equity Ratio, Debt To Asset Ratio and Tangible Assets Debt Coverage). Data Analysis In this study, the descriptive statistical test, normality test, and hypothesis testing were carried out using the paired sample t-test and the Wilcoxon Signed Rank Test. The results of the study show that the financial performance conditions of 58 companies in the consumer goods industry sector prove that there are significant differences in the profitability ratios, there are no significant differences in the liquidity ratios, there are no significant differences in the solvency ratios, and there are significant differences in the activity ratios. between before the pandemic in 2019 and during the pandemic in 2020. Keywords : financial performance, ratios, pandemic Covid-19